Failure of a Vagus Nerve Stimulator following a Nearby Lightning Strike - Terry, Garth E.; Conry, Joan A.; Taranto, Eleanor; Yaun, Amanda (Pediatric neurosurgery, 2011)
We recently reported our experience with implanted vagus nerve stimulators (VNS) in 62 children over a 7-year period. Here, we present a case of a VNS that successfully reduced the number and severity of seizures in a patient with an unusual seizure pattern, and failed to function shortly after a lightning storm. To our knowledge, the failure of VNS or any implantable electrical devices by lightning has not been reported in the literature. This mechanism of electrical interference, while unusual, may require more attention as these devices are expected to be used more frequently.